Front line public diplomacy : how US embassies communicate with foreign publics - Rugh, William A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Front Line Public Diplomacy explains how American diplomats at US embassies abroad communicate with foreign publics to support American national interests, countering misperceptions and hostile portrayals of our country.
Keywords: Social sciences; Cultural policy; Political science; International relations; International organization; Diplomacy; Economic policy; Social Sciences; Development Policy; International Relations; International Organization; Diplomacy; Political Science; Cultural Policy